3 µm Water vapor self- and foreign-continuum: New method for determination and new insights into the self-continuum. (September 2020) - Birk, M.; Wagner, G.; Loos, J.; Shine, K.P.
Highlights: New method for continuum determination. High resolution in-band foreign- and self-continua in 3 µm region. Continua with complete spectral coverage without gaps. Improved model of self-continuum using generic ro-vibrational band shapes. Abstract: The H2 O self- and foreign- in-band continua in the region 3400–3900 cm −1 were experimentally determined for 296 and 353 K from multispectrum fitting results of line parameters using the Hartmann-Tran line profile (HTP) and Rosenkranz line mixing. The continua were extracted from the baselines which were determined in the microwindow-based multispectrum fits. Continua were then obtained by simultaneous fitting of all baselines from measurements containing continuum information. The self-continuum at 296 K was determined from self-broadened measurements and agrees with that determined from air broadened measurements. The overall shape and strength of the new self-continuum agrees with the CAVIAR results between 3600 and 3800 cm -1 but differences exceed the stated uncertainties at higher and lower wavenumbers. Moreover, the new self-continuum is much smoother, has no gaps and is obtained with a high resolution of 2.4 cm −1 . The self-continuum was fitted as sum of modeled bound and quasi-bound dimer spectra. From rotational constants, the bound dimer parallel and perpendicular band shapes of the near prolate symmetric top molecule were calculated and used as kernels to fit fundamental wavenumbers, relative band intensities and partitioning of parallel and perpendicular band type, while the integral of the band intensities of the four fundamentals was fixed to published experimental/theoretical data. A dimerization constant for the bound dimer of KDb = 0.026(2) atm −1 and the quasi-bound dimer of KDq = 0.044(5) atm −1 was derived from the fits. The foreign-continuum has no gaps, a spectral resolution of 6–16 cm −1, and is about 40% smaller than the MT_CKD3.2 continuum model. It has a distinctly different shape showing a pronounced P-Q-R branch structure. The foreign-continuum shape is narrower than the monomer band shape which is also true for the MT_CKD3.2 continuum model. The CAVIAR foreign-continuum is much noisier but on average is in good agreement with the new measurements.